The influence of social media and cultural ideals on body dysmorphic disorder among adult males in the UAE - Haj Hussain, Kholod; Al Midani, Abdul Rahman; Abdallah, Mohamad; Alyassi, Aisha; Alzubaidy, Haya; Alrashed, Shahad; Muhammad, Jibran Sualeh; Alhaj, Hamid A. (Frontiers in Psychiatry, 2025)
IntroductionBody Dysmorphic Disorder (BDD) is a psychiatric condition characterized by an excessive preoccupation with perceived flaws in physical appearance, often resulting in significant emotional distress and impaired functioning. Although social influences are believed to contribute to the development of BDD, their specific impact remains underexplored, especially among males in the Middle East. This study aims to investigate the relationship between BDD symptoms and social factors, with a particular emphasis on the role of social media among adult males in the United Arab Emirates (UAE).MethodsA cross-sectional survey was conducted among men using a self-administered 30-item questionnaire. The instrument covered demographics, the Body Dysmorphic Disorder Questionnaire (BDDQ), body image and cosmetic surgery attitudes, social media use, and exercise behaviors. The questionnaire was translated using a forward-backward translation technique and reviewed for clarity and cultural appropriateness in accordance with WHO guidelines. Bivariate analyses were conducted to explore associations between variables. Chi-square and Fisher’s exact tests were used for categorical variables, and t-tests for continuous variables, with statistical significance set at p < 0.05.ResultsOf the 403 participants, 53 (13.2%) met the BDDQ cutoff criteria, and 15 (3.7%) screened positive for BDD (excluding weight-related concerns). A significant association was found between BDD screening positivity and perceived negative impact of social media (χ²(2) = 19.92, p <.001). Similarly, perceived cultural pressure to attain an ideal appearance was significantly associated with higher BDDQ positivity. Participants who screened positive for BDD were significantly more likely to report physical discomfort (OR = 4.9, 95% CI: [1.5, 15.8], p = 0.005), concern about others’ perceptions of their bodies (OR = 3.9, 95% CI: [1.2, 12.3], p = 0.017), and interest in cosmetic surgery (OR = 5.8, 95% CI: [2.0, 16.4], p = 0.002). Multivariate analysis showed that perceived negative social media impact, specific cosmetic concerns, and lower BMI were independent predictors of BDD.ConclusionsThis study highlights the significant role of social media, cultural appearance pressures, and attitudes toward cosmetic surgery in the manifestation of BDD symptoms among males in the UAE. Culturally sensitive public health initiatives should focus on promoting healthy body image and increasing awareness of BDD.